A Biomimetic Synthesis of des-Hydroxy Paecilospirone - Feng, Zhen-Gao; Burnett, G. Leslie; Pettus, Thomas R. R. (Synlett, 2018)
The carbon framework of des-hydroxy paecilospirone was rapidly synthesized using a biomimetic approach whereby an enol ether and an ortho-quinone methide (o-QM), each derived from the same lactone, were combined to arrive at the complete carbon skeleton of paecilospirone.
Keywords: ortho-quinone methide; Diels–Alder; paecilospirone; benzylic oxidation; enol ether